Land Injection Vs Land Conversion: Seeking the Solution to the Discontinuity of Agricultural Land Provision - Pujiriyani, Dwi Wulan; Soetarto, Endriatmo (Marcapada: Jurnal Kebijakan Pertanahan, 2022)
Land conversion takes place more rapidly than the addition of new land. This paper attempts to investigate these two events by offering a more sensible solution to answer the need for land provision which over time continues to clash with various interests in land. The best solution to land provision is to give recognition to the ‘living space and the farming profession' by stating that the agricultural profession is the noblest profession, the most realistic profession, and constitutionally justified. They are a group of people whose profession is on going, or continuing, and it only requires political commitment as well as recognition of their living space and their profession that farmers and farming are a profession as well as a right to life. Local initiatives such as those emerging in the Kasepuhan community, the Subak tradition in Bali, and the determination of Sedulur Sikep community with their farming traditions should have earned their right not to be ‘disturbed’ but to be let live and get recognition and protection. Protecting these existing and sustainable forms of local farming initiatives is a real manifestation of the solution to the deadlock of the search for new agricultural land that faces various obstacles. Recognition should not only be given to indigenous groups as it has been done, but also to food farmer communities that have independently developed their agriculture in a sustainable manner.